Analysis And Design Of Application Of Sales And Control Of Stock Of Daily Goods With Rop (Reorder Point) Method - Annisak Izzaty Jamhur; Novi Trisna; Yesri Elva (Journal of Applied Engineering and Technological Science (JAETS), 2020)
In the era of globalization now developments in the field of information technology are increasingly rapid. No wonder now more and more shops are starting to develop their administrative systems using information technology and one of them is a shop in the field of daily goods. Some stores use various ways to attract as many customers as possible. So that the data processing is slow and shop owners often have difficulty in finding data that has been processed. To provide satisfactory services for customers, it is necessary to reform several systems, including information systems for sales, purchasing, making daily, monthly, annual sales reports, and inventory data reports using the ROP (Reorder Point) method and designing using the ASI model (System Analysis Information), while the process of making a desktop program or application uses the VISUAL BASIC.NET 2010 programming language that is supported by the MySQL database.